Performance of universal adhesives on bonding to leucite-reinforced ceramic - Kim, Ryan Jin-Young; Woo, Jung-Soo; Lee, In-Bog; Yi, Young-Ah; Hwang, Ji-Yun; Seo, Deog-Gyu (Biomaterials research, 2015)
Background This study aimed to investigate the microshear bond strength of universal bonding adhesives to leucite-reinforced glass-ceramic. Methods Leucite-reinforced glass-ceramic blocks were polished and etched with 9.5% hydrofluoric acid for 1 min. The specimens were assigned to one of four groups based on their surface conditioning (n = 16): 1) NC: negative control with no further treatment; 2) SBU: Single Bond Universal (3M ESPE); 3) ABU: ALL-BOND Universal (Bisco); and 4) PC: RelyX Ceramic Primer and Adper Scotchbond Multi-Purpose Adhesive (3M ESPE) as a positive control. RelyX Ultimate resin cement (3M ESPE) was placed on the pretreated ceramic and was light cured. Eight specimens from each group were stored in water for 24 h, and the remaining eight specimens were thermocycled 10,000 times prior to microshear bond strength evaluation. The fractured surfaces were examined by stereomicroscopy and scanning electron microscopy (SEM). Results After water storage and thermocycling, the microshear bond strength values decreased in the order of PC > SBU and ABU > NC (P < 0.05). Thermocycling significantly reduced the microshear bond strength, regardless of the surface conditioning used (P < 0.05). Cohesive failure in the ceramic and mixed failure in the ceramic and resin cement were observed in the fractured specimens. The percentage of specimens with cohesive failure after 24 h of water storage was: NC (50%), SBU (75%), ABU (75%), and PC (87%). After thermocycling, the percentage of cohesive failure in NC decreased to 25%; however, yet the percentages of the other groups remained the same. Conclusions Although the bond strength between resin and hydrofluoric acid-etched glass ceramic was improved when universal adhesives were used, conventional surface conditioning using a separate silane and adhesive is preferable to a simplified procedure that uses only a universal adhesive for cementation of leucite-reinforced glass-ceramic.